The impact of optimism on usage of computer based accounting practices among small scale enterprises - Rathnayake, R. M. M. P. (IJRDO - Journal of Applied Management Science, 2015)
In most parts of developed countries, it is almost impossible to function as an accountant without requisite Information Technology skills. Advent of the computerized accounting practices equally affected to the organizations in both developed and developing countries. As introducing new technologies, the manual accounting systems have become gradually inadequate for decision needs. The major objective of the research paper is to explore the impact of Optimism of small business owners on their Usage of Computer based Accounting Practices among small scale businesses. Moreover, it tries to evaluate the level of Optimism regarding the Technology and the level of the Usage of Computer based Accounting Practices among small scale businesses. And ultimately it tries to find out the relationship between Optimism and the Usage of Computer based Accounting Practices among the small scale businesses. The study was conducted among the sample of hundred small business owners who were randomly selected from Nuwara Eliya district. The data analysis included the Univariate analysis (descriptive), Cross Tabulation analysis and Bivariate analysis. Considering the variable, Usage of Computer Based Accounting Practices among small scale businesses in Nuwara Eliya district is in low level but the influence of the Optimism regarding the Technology is in high level. The Pearson‟s correlation analysis explores that there is a positively significant linear relationship between Optimism regarding the Technology and the Usage of Computer based Accounting Practices. Regression analysis has proved that Optimism regarding the Technology of small business owners shall be considered as a strategic tool and major predictor of Usage of Computer based Accounting Practices among small businesses in Nuwara Eliya district.